The generation of human induced pluripotent stem cell lines from individuals of Black African ancestry in South Africa - Jerolen Naidoo; Tracey Hurrell; Janine Scholefield (Stem Cell Research)
The lack of equitable representation of African diversity in scientific resources, such as genome-wide association studies and human induced pluripotent stem cell (hiPSC) repositories, has perpetuated inequalities in the advancement of health research. HiPSCs could be transformative in regenerative and precision medicine, therefore, the generation of diverse lines is critical in the establishment of African-relevant preclinical cellular models. HiPSC lines were derived from two healthy donors of Black African ancestry using Sendai virus reprogramming of dermal fibroblasts, and characterised to confirm stemness markers, trilineage differentiation, and genetic integrity. These hiPSCs represent a valuable resource for modelling African relevant disease biology.